Representation of inner, outer and expanding circle varieties and cultures in global ELT textbooks - Zia Tajeddin (Asian-Pacific Journal of Second and Foreign Language Education, 2020)
Abstract The rise of world Englishes has challenged the emphasis on native-speaker accents and cultures in English language teaching. This study aimed to investigate the representation of world Englishes and cultures in three global language teaching textbooks, namely Interchange, English Result, and American English File. The textbooks were subjected to content analysis regarding their reference to Inner, Outer, and Expanding Circles’ varieties and their associated cultural contents. Kachru (The alchemy of English: The spread functions and models of non-native Englishes. Oxford: Pergamon, 1986) notion of Concentric Circles, and the categorization proposed by Pfister and Borzelli (Unterrichtspraxis 10:102–108, 1977) functioned as a framework to see which aspects of each culture (social, personal, religion/arts/humanities, political systems and institutions, and environmental concerns) were addressed in these textbooks. Findings revealed that most of the references to the three circles and cultural elements embodied in the textbooks were toward Inner Circle countries in American English File. Furthermore, in Interchange and English Result series, reference to Outer and Expanding Circles’ varieties and cultural elements were comparatively more evident. However, all the three textbook series mostly represented Inner-Circle accents. These findings have implications for materials developers to adopt an EIL-aware approach and to avoid the sole representation of native speakers’ linguistic norms and cultures in ELT textbooks.